Integrated environmental analysis of the main cork products in southern Europe (Catalonia – Spain) - Rives, Jesús; Fernandez-Rodriguez, Ivan; Rieradevall, Joan; Gabarrell, Xavier (Journal of Cleaner Production)
This study presents an environmental analysis of the cork sector by integrating and evaluating the production of the products that are most commonly made of cork: natural cork stoppers, champagne cork stoppers, white cork granulate and black cork granulate, in order to propose environmental strategies that could contribute to minimising the potential impacts of the cork sector. Life Cycle Assessment (LCA) was the methodology used in order to assess the potential environmental impacts of the cork sector and its main products. Inventory was supported by 15 companies in Catalonia. Different environmental midpoint impact categories were reported and analysed according to CML 2001 method such as Abiotic Depletion (ADP), Acidification Potential (AP), Eutrophication Potential (EP), and many other. Also, the Global Warming Potential (GWP 100 years), was assessed, and it was found that the cork sector contributed to fixing carbon dioxide and consequently can help to mitigate climate change, besides generating cork products. Specifically, 3.4 tonnes of CO2 eq. were emitted to convert a tonne of raw cork from the forest into products, while 18 tonnes of CO2 are fixed per tonne as a result of the existence of cork oak forests; the resulting balance was that 14.6 tonnes of CO2 are fixed. A sensitivity analysis was carried out of the distribution of environmental impacts between products; it was observed that allocation rules were an important point of the assessment. The use of cork, a natural, renewable and local material, can help to reduce the environmental impact of products. The use of cork stoppers contributes to reducing the carbon footprint of beverages such as wines, champagnes, beers, ciders, brandies and many other beverages.
Keywords: agro-forestry system; Carbon dioxide; Champagne cork stopper; Cork sector; Environmental impact; Life cycle assessment (LCA); Mediterranean; natural cork stopper

Environmental analysis of raw cork extraction in cork oak forests in southern Europe (Catalonia--Spain). - Rives, Jesús; Fernandez-Rodriguez, Ivan; Rieradevall, Joan; Gabarrell, Xavier (Journal of environmental management, 2012)
Cork oak grows endemically in a narrow region bordering the western Mediterranean, and especially in the Iberian Peninsula. The importance of cork agro-forestry systems lies in the fact that a natural and renewable raw material - cork - can be extracted sustainably without endangering the tree or affecting biodiversity. This paper describes an environmental analysis of the extraction of raw cork in cork oak forests in Catalonia, using data from five representative local forest exploitations. The evaluation was carried out using life cycle assessment (LCA) methodology, and all the forestry management required to obtain a tonne of raw cork was included. The aim of the study was to evaluate the environmental impacts - in terms of global warming, acidification, eutrophication, human toxicity, and so on - caused by cork extraction and determine the carbon dioxide balance of these forestry systems, with a tree lifespan of about 200 years. During the life cycle extraction of cork in Catalonia, 0.2 kg of CO(2) eq. was emitted per kg of raw cork extracted. Moreover, cork cannot be extracted without the tree, which will be fixing carbon dioxide throughout its technological useful life (200 years), despite the fact that the bark is removed periodically: every 13-14 years. If the emission from extraction and the carbon contained in the material is discounted, the carbon dioxide balance indicates that 18 kg of CO(2) are fixed per kg of raw cork extracted. Therefore, cork is a natural, renewable and local material that can replace other non-renewable materials, at local level, to reduce the environmental impacts of products, and particularly to reduce their carbon footprint.
Keywords: agro-forestry system; Carbon dioxide; Climate change mitigation; Cork Oak Forest; Life cycle assessment (LCA); Mediterranean

Modelling the drought impact on monoterpene fluxes from an evergreen Mediterranean forest canopy. - Grote, Rüdiger; LAVOIR, ANNE-VIOLETTE; Rambal, Serge; Staudt, Michael; Zimmer, Ina; Schnitzler, Jörg-Peter (Oecologia, 2009)
In many ecosystems drought cycles are common during the growing season but their impact on volatile monoterpene emissions is unclear. Therefore, we aimed to develop and evaluate a process-based modelling approach to explore the explanatory power of likely mechanisms. The biochemically based isoprene and monoterpene emission model SIM-BIM2 has been modified and linked to a canopy model and a soil water balance model. Simulations are carried out for Quercus ilex forest sites and results are compared to measured soil water, photosynthesis, terpene-synthase activity, and monoterpene emission rates. Finally, the coupled model system is used to estimate the annual drought impact on photosynthesis and emission. The combined and adjusted vegetation model was able to simulate photosynthesis and monoterpene emission under dry and irrigated conditions with an R(2) of 0.74 and 0.52, respectively. We estimated an annual reduction of monoterpene emission of 67% for the extended and severe drought period in 2006 in the investigated Mediterranean ecosystem. It is concluded that process-based ecosystem models can provide a useful tool to investigate the involved mechanisms and to quantify the importance of specific environmental constraints.
Keywords: Biological; Carbon dioxide; Carbon Dioxide: metabolism; Computer Simulation; Drought impact; Droughts; France; Model coupling; Models; monoterpene emission; Monoterpenes; Monoterpenes: metabolism; photosynthesis; Photosynthesis: physiology; Plant Leaves; Plant Leaves: metabolism; Quercus; Quercus ilex (holm oak); Quercus: metabolism; Scaling; Trees; Trees: metabolism; water; Water: metabolism

Dynamics of the enhanced emissions of monoterpenes and methyl salicylate, and decreased uptake of formaldehyde, by Quercus ilex leaves after application of jasmonic acid - Filella, Iolanda; Penuelas, Josep; Llusia, Joan (New Phytologist, 2006)
* • Jasmonic acid (JA) is a signalling compound with a key role in both stress and development in plants, and is reported to elicit the emission of volatile organic compounds (VOCs). Here we studied the dynamics of such emissions and the linkage with photosynthetic rates and stomatal conductance. * • We sprayed JA on leaves of the Mediterranean tree species Quercus ilex and measured the photosynthetic rates, stomatal conductances, and emissions and uptake of VOCs using proton transfer reaction mass spectrometry and gas chromatography after a dark–light transition. * • Jasmonic acid treatment delayed the induction of photosynthesis and stomatal conductance by approx. 20 min, and decreased them 24 h after spraying. Indications were found of both stomatal and nonstomatal limitations of photosynthesis. Monoterpene emissions were enhanced (20–30%) after JA spraying. Jasmonic acid also increased methyl salicylate (MeSa) emissions (more than twofold) 1 h after treatment, although after 24 h this effect had disappeared. Formaldehyde foliar uptake decreased significantly 24 h after JA treatment. * • Both biotic and abiotic stresses can thus affect plant VOC emissions through their strong impact on JA levels. Jasmonic acid-mediated increases in monoterpene and MeSa emissions might have a protective role when confronting biotic and abiotic stresses.
Keywords: Carbon dioxide; Carbon Dioxide: metabolism; Cyclopentanes; Cyclopentanes: pharmacology; Dehydration; Formaldehyde; Formaldehyde: metabolism; jasmonic acid (JA); light; methyl salicylate; Monoterpenes; Monoterpenes: metabolism; net photosynthetic rates; Oxylipins; photosynthesis; Plant Leaves; Plant Leaves: drug effects; Plant Leaves: metabolism; Quercus; Quercus ilex (holm oak); Quercus: drug effects; Quercus: metabolism; Salicylates; Salicylates: metabolism; Stomatal conductance; Temperature; VOC (volatile organic compound)

Dynamics of the enhanced emissions of monoterpenes and methyl salicylate, and decreased uptake of formaldehyde, by Quercus ilex leaves after application of jasmonic acid - Filella, Iolanda; Penuelas, Josep; Llusia, Joan (New Phytologist, 2006)
* • Jasmonic acid (JA) is a signalling compound with a key role in both stress and development in plants, and is reported to elicit the emission of volatile organic compounds (VOCs). Here we studied the dynamics of such emissions and the linkage with photosynthetic rates and stomatal conductance. * • We sprayed JA on leaves of the Mediterranean tree species Quercus ilex and measured the photosynthetic rates, stomatal conductances, and emissions and uptake of VOCs using proton transfer reaction mass spectrometry and gas chromatography after a dark–light transition. * • Jasmonic acid treatment delayed the induction of photosynthesis and stomatal conductance by approx. 20 min, and decreased them 24 h after spraying. Indications were found of both stomatal and nonstomatal limitations of photosynthesis. Monoterpene emissions were enhanced (20–30%) after JA spraying. Jasmonic acid also increased methyl salicylate (MeSa) emissions (more than twofold) 1 h after treatment, although after 24 h this effect had disappeared. Formaldehyde foliar uptake decreased significantly 24 h after JA treatment. * • Both biotic and abiotic stresses can thus affect plant VOC emissions through their strong impact on JA levels. Jasmonic acid-mediated increases in monoterpene and MeSa emissions might have a protective role when confronting biotic and abiotic stresses.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd accession-num: 16390425
Keywords: Carbon dioxide; Carbon Dioxide: metabolism; Cyclopentanes; Cyclopentanes: pharmacology; Dehydration; Formaldehyde; Formaldehyde: metabolism; jasmonic acid (JA); light; methyl salicylate; Monoterpenes; Monoterpenes: metabolism; net photosynthetic rates; Oxylipins; photosynthesis; Plant Leaves; Plant Leaves: drug effects; Plant Leaves: metabolism; Quercus; Quercus ilex (holm oak); Quercus: drug effects; Quercus: metabolism; Salicylates; Salicylates: metabolism; Stomatal conductance; Temperature; VOC (volatile organic compound)

Study of some characteristic Mediterranean vegetation species best suited for renaturalization of terminal-phase municipal solid waste (MSW) landfills in Puglia (Southern Italy) - De Mei, Massimiliano; Di Mauro, Mariaida (Acta Oecologica, 2006)
Natural recovery of worked-out or closed municipal solid waste (MSW) landfills is a current topic, but knowledge about the adaptability of Mediterranean vegetation species to such stressful conditions is still quite poor. Autochthonous plants were selected to withstand the stresses such as hot climate and drought typical of Mediterranean areas; this characteristic potentially allows the plants an easier, efficient adaptation. Our aim was to provide information in order to obtain an adequate quality of environmental renewal of a landfill and a reduced management cost while ensuring rehabilitation to an acceptable naturalistic state. The investigation lasted 3 years; some Mediterranean scrub native plant species were selected and monitored in their morphological (total and relative height, basal diameter, number of inter-nodes) and physiological (photosynthetic rate and water potential) activity. In order to test dependence on CO2 concentration, different meteorological parameters were also monitored. Ceratonia siliqua, Phillyrea latifolia, Olea europaea and Quercus ilex showed considerable adaptability, reacting positively to every improvement in environmental conditions, particularly those of a meteorological nature. Survival and growth was satisfactory in Hedysarum coronarium, Medicago sativa, Lotus corniculatus, Rosmarinus officinalis, Myrtus communis and Viburnum tinus. Fraxinus ornus and Acer campestre suffered stress during the summer dry period and recovered quickly when atmospheric conditions improved. A drop irrigation system to ensure a satisfactory soil moisture during summer dry periods was the fundamental element for survival
Keywords: Biogas; Carbon dioxide; Carbon dioxide concentration; climate; Gramineae; herbaceous; Landfills; Leguminosae; photosynthesis; Plant morphology; Precipitation; Scrub arboreal species; Soil; Temperature; water potential

Study of some characteristic Mediterranean vegetation species best suited for renaturalization of terminal-phase municipal solid waste (MSW) landfills in Puglia (Southern Italy) - De Mei, Massimiliano; Di Mauro, Mariaida (Acta Oecologica, 2006)
Natural recovery of worked-out or closed municipal solid waste (MSW) landfills is a current topic, but knowledge about the adaptability of Mediterranean vegetation species to such stressful conditions is still quite poor. Autochthonous plants were selected to withstand the stresses such as hot climate and drought typical of Mediterranean areas; this characteristic potentially allows the plants an easier, efficient adaptation. Our aim was to provide information in order to obtain an adequate quality of environmental renewal of a landfill and a reduced management cost while ensuring rehabilitation to an acceptable naturalistic state. The investigation lasted 3 years; some Mediterranean scrub native plant species were selected and monitored in their morphological (total and relative height, basal diameter, number of inter-nodes) and physiological (photosynthetic rate and water potential) activity. In order to test dependence on CO2 concentration, different meteorological parameters were also monitored. Ceratonia siliqua, Phillyrea latifolia, Olea europaea and Quercus ilex showed considerable adaptability, reacting positively to every improvement in environmental conditions, particularly those of a meteorological nature. Survival and growth was satisfactory in Hedysarum coronarium, Medicago sativa, Lotus corniculatus, Rosmarinus officinalis, Myrtus communis and Viburnum tinus. Fraxinus ornus and Acer campestre suffered stress during the summer dry period and recovered quickly when atmospheric conditions improved. A drop irrigation system to ensure a satisfactory soil moisture during summer dry periods was the fundamental element for survival
Keywords: Biogas; Carbon dioxide; Carbon dioxide concentration; climate; Gramineae; herbaceous; Landfills; Leguminosae; photosynthesis; Plant morphology; Precipitation; Scrub arboreal species; Soil; Temperature; water potential

A field system to deliver desired O-3 concentrations in leaf-level gas exchange measurements: Results for Holm oak near a CO2 spring - Grulke, N. E.; Paoletti, E. (PHYTON-ANNALES REI BOTANICAE, 2005)
Conventional gas exchange systems adsorb ozone (O-3) despite attempts to saturate the system prior to measurements. A steady-state, open photosynthetic system was designed and used in the field to supply a small leaf cuvette with conditioned air stream (growth CO2 concentrations, humidified, cooled) and augmented with either background or elevated O-3. Two innovations led to success: 1) supplying the cuvette with cooled air instead of Peltier cooling within the cuvette; and 2) using a custom-designed, low flow (capable of 100 seem), fast response (20 S) O-3 monitor. We tested whether elevated CO2 would alter stomatal response to short term, steady state elevated O-3. Holm oak (Quercus ilex L., Fagaceae), an evergreen broadleaf tree growing near a geothermal CO2 vent, has been exposed over its lifetime to a gradient of CO2 concentrations. We chose trees in areas averaging 450 mu l 1(-1) (low background CO2) and 1500 mu l 1(-1) (super-elevated CO2). Background O-3 exposure at this site is moderate (10 am to 5 pm averages of 62 nl 1(-1) in June). We measured gas exchange at the growth CO2 levels, and at ambient O-3 or 1.7x ambient O-3 concentrations. At low background CO2, short term elevated O-3 depressed foliar transpiration. Because there was little concurrent change in net assimilation, instantaneous transpiration efficiency was increased. At super-elevated CO2, short term elevated O-3 did not affect foliar transpiration. Because there was a concurrent decrease in net assimilation, instantaneous transpiration efficiency was decreased at elevated CO2 and O-3.
The following values have no corresponding Zotero field: pub-location: WIENER STRASSE 21-23, A-3580 HORN, AUSTRIA publisher: FERDINAND BERGER SOEHNE
Keywords: Carbon dioxide; instantaneous transpiration efficiency; ozone exposure; Quercus ilex

Mediterranean natural forest living at elevated carbon dioxide: soil biological properties and plant biomass growth - Moscatelli, M C; Fonck, M; De Angelis, P; Larbi, H; Macuz, A; Rambelli, A; Grego, S (Soil Use and Management, 2001)
Abstract. Biomass productivity and soil microbial responses to long-term CO2 enrichment have been investigated in a Mediterranean natural forest ecosystem. Several biochemical parameters have been measured on soil samples taken from six open top chambers (OTCs), enclosing clumps of natural Mediterranean woody vegetation including: Quercus ilex L., Phillyrea angustifolia L., Pistacia lentiscus L. and Myrtus communis L. The CO2 concentration of the air inside the OTCs was either ambient or ambient plus 350 μmol mol–1 (c. 710 ppm as mean daily value). Microbial C biomass, microbial respiration, dehydrogenase, β-glucosidase, acid phosphatase and protease activities, inorganic N and soluble P, were tested in order to evaluate soil microbial size and activity. Statistically correlated seasonal patterns have been identified in some biochemical parameters in response to climatic conditions, soil nutritional status and the physiology of the vegetative cover. In situ soil respiration and above- and below-ground productivity were also measured. Microbial responses to CO2 enrichment were observed only at the beginning of the study and a general progressive reduction of the CO2 effect was recorded as monitoring continued. These results are in agreement with data from literature regarding similar studies on natural complex communities.
Keywords: Carbon dioxide; Forests; Mediterranean Region; microbial activities; roots; Soil; Soil enzymes

Mediterranean natural forest living at elevated carbon dioxide: soil biological properties and plant biomass growth - Moscatelli, M. C.; Fonck, M.; De Angelis, P.; Larbi, H.; Macuz, A.; Rambelli, A.; Grego, S. (Soil Use and Management, 2001)
Abstract. Biomass productivity and soil microbial responses to long-term CO2 enrichment have been investigated in a Mediterranean natural forest ecosystem. Several biochemical parameters have been measured on soil samples taken from six open top chambers (OTCs), enclosing clumps of natural Mediterranean woody vegetation including: Quercus ilex L., Phillyrea angustifolia L., Pistacia lentiscus L. and Myrtus communis L. The CO2 concentration of the air inside the OTCs was either ambient or ambient plus 350 μmol mol–1 (c. 710 ppm as mean daily value). Microbial C biomass, microbial respiration, dehydrogenase, β-glucosidase, acid phosphatase and protease activities, inorganic N and soluble P, were tested in order to evaluate soil microbial size and activity. Statistically correlated seasonal patterns have been identified in some biochemical parameters in response to climatic conditions, soil nutritional status and the physiology of the vegetative cover. In situ soil respiration and above- and below-ground productivity were also measured. Microbial responses to CO2 enrichment were observed only at the beginning of the study and a general progressive reduction of the CO2 effect was recorded as monitoring continued. These results are in agreement with data from literature regarding similar studies on natural complex communities.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: Carbon dioxide; Forests; Mediterranean Region; microbial activities; roots; Soil; Soil enzymes

Influence of increased atmospheric CO2 concentration on quality of plant material and litter decomposition - Coûteaux, Marie-Madeleine; Kurz, Cathy; Bottner, Pierre; Raschi, Antonio (Tree Physiology, 1999)
Nitrogen (N) and lignin concentrations in plant tissues and litter of plants grown in greenhouses or open-top chambers in elevated atmospheric CO2 concentration were compared with those of plants grown in ambient air in short-term studies. We also compared the N concentration of plant material of Quercus ilex L. and Q. pubescens Willd. growing in the vicinity of natural CO2-springs with that of the same species growing at a control site. In the short-term studies, elevated CO2 caused significant decreases in tissue N concentration and the extent of the decrease varied with species. Nitrogen amendment of the soil lessened the CO2-enrichment effect. Lignin concentration was modified by elevated CO2 and the effect was species specific, but no general positive or negative trend was evident. A comparison of trees growing under natural conditions near a natural CO2-spring and at a control site revealed no site differences in N concentration of the plant material. A comparison of published results on decomposition rates of litter produced in elevated atmospheric CO2 and in ambient air indicated that CO2 enrichment can cause both enhancements and decreases of carbon mineralization. We conclude that (1) long-term responses to elevated CO2 could differ from the results obtained from short-term studies and that (2) biodiversity could be an important factor altering the sign of the feedback on atmospheric CO2 concentration. We also discuss the implications of our finding of a long-term, inhibitory effect of the initial N concentration of litter on the decomposition rate of litter and its consequence on ecosystem feedback.
10.1093/treephys/19.4-5.301
Keywords: Biodiversity; Carbon dioxide; Global change; lignin content; nitrogen content

Influence of increased atmospheric CO2 concentration on quality of plant material and litter decomposition - Coûteaux, Marie-Madeleine; Kurz, Cathy; Bottner, Pierre; Raschi, Antonio (Tree Physiology, 1999)
Nitrogen (N) and lignin concentrations in plant tissues and litter of plants grown in greenhouses or open-top chambers in elevated atmospheric CO2 concentration were compared with those of plants grown in ambient air in short-term studies. We also compared the N concentration of plant material of Quercus ilex L. and Q. pubescens Willd. growing in the vicinity of natural CO2-springs with that of the same species growing at a control site. In the short-term studies, elevated CO2 caused significant decreases in tissue N concentration and the extent of the decrease varied with species. Nitrogen amendment of the soil lessened the CO2-enrichment effect. Lignin concentration was modified by elevated CO2 and the effect was species specific, but no general positive or negative trend was evident. A comparison of trees growing under natural conditions near a natural CO2-spring and at a control site revealed no site differences in N concentration of the plant material. A comparison of published results on decomposition rates of litter produced in elevated atmospheric CO2 and in ambient air indicated that CO2 enrichment can cause both enhancements and decreases of carbon mineralization. We conclude that (1) long-term responses to elevated CO2 could differ from the results obtained from short-term studies and that (2) biodiversity could be an important factor altering the sign of the feedback on atmospheric CO2 concentration. We also discuss the implications of our finding of a long-term, inhibitory effect of the initial N concentration of litter on the decomposition rate of litter and its consequence on ecosystem feedback.
10.1093/treephys/19.4-5.30110.1093/treephys/19.4-5.301
Keywords: Biodiversity; Carbon dioxide; Global change; lignin content; nitrogen content

Effects of elevated carbon dioxide on leaf gas exchange and growth of cork-oak (Quercus suber L) seedlings - Damesin, C; Galera, C; Rambal, S; Joffre, R (Ann. For. Sci., 1996)
Leaf gas exchange and growth were determined on cork-oak (Quercus suber L) seedlings which were grown from acorns for periods of up to 4 months in greenhouses at ambient (350 μmol mol-1) and at elevated (700 μmol mor-1) concentrations of carbon dioxide. In well-watered conditions, daily maximum photosynthesis (15 μmol m-2 s -1) and stomatal conductance (440 mmol m-2 s-1) of plants grown and measured at 700 μmol mol-1 CO2 did not differ from those of plants grown and measured at 350 μmol mol-1. In conditions of moderate drought, net CO2 assimilation was at least twice as great in elevated CO2, but stomatal conductance was unchanged. Elevated CO2 affected total biomass production, the average increase being 76 and 97% at 3 and 4 months, respectively. Shoot biomass, root biomass, stem height and total leaf area were increased by elevated CO2. Root and stem ramification were also enhanced by elevated CO2, but no change in root/shoot ratio was observed.
Keywords: Carbon dioxide; Growth; photosynthesis; Quercus suber; Stomatal conductance

Carbon dioxide efflux and pCO 2 in soils of threeQuercus ilex montane forests - Piñol, J.; Alcañiz, J. M.; Roda, F. (Biogeochemistry, 1995)
Soil CO2 efflux and pCO2 in the soil atmosphere were measured during one year at three montane sites of Mediterranean sclerophyllous forests in NE Spain. Two sites were located in the upper and lower slopes of a small catchment in the Prades mountains (mean precipitation 550 mm year-'), and a third site was located on a lower slope in the Montseny mountains (mean precipitation 900 mm year-'). The three sites were similar in bedrock and vegetation, but differed in soil characteristics and water availability. Seasonal variation of CO2 efflux and soil pCO2 were affected by soil temperature and, to a lesser extent, by soil moisture. Annual mean soil CO2 efflux (considered as soil respiration) was similar at Montseny and at the comparably located site at Prades (83 ± 18 S.E. vs. 75 4 9 mg CO2 m - 2 hour- , respectively), and was highest at the Prades upper slope site (122 ± 22 mg CO2 m -2 hour-l). Despite those relatively similar CO 2 effluxes, mean soil pCO2 was much higher at both Prades sites than at Montseny. Soil pCO2 always increased with depth at Prades while maxima pCO2 at Montseny were often at 20-30 cm depth. A model based on gas diffusion theory was able to explain why soil pCO2 was much higher at Prades than at Montseny, and to reproduce the shape of the vertical profile of pCO2 at the Prades soils. Nevertheless, the model failed to simulate the soil pCO2 maximum found at 20-30 cm depth at the Montseny site. Model simulations using a time-variable CO2 production rate suggested that pCO2 maxima at intermediate depth could be the result of a transient situation instead of an equilibrium one.
Keywords: carbon cycle; Carbon dioxide; Mediterranean ecosystems; soil atmosphere; Soil respiration

Carbon dioxide efflux and pCO 2 in soils of threeQuercus ilex montane forests - Piñol, J; Alcañiz, J M; Rodà, F (Biogeochemistry, 1995)
Soil CO2 efflux and pCO2 in the soil atmosphere were measured during one year at three montane sites of Mediterranean sclerophyllous forests in NE Spain. Two sites were located in the upper and lower slopes of a small catchment in the Prades mountains (mean precipitation 550 mm year-'), and a third site was located on a lower slope in the Montseny mountains (mean precipitation 900 mm year-'). The three sites were similar in bedrock and vegetation, but differed in soil characteristics and water availability. Seasonal variation of CO2 efflux and soil pCO2 were affected by soil temperature and, to a lesser extent, by soil moisture. Annual mean soil CO2 efflux (considered as soil respiration) was similar at Montseny and at the comparably located site at Prades (83 ± 18 S.E. vs. 75 4 9 mg CO2 m - 2 hour- , respectively), and was highest at the Prades upper slope site (122 ± 22 mg CO2 m -2 hour-l). Despite those relatively similar CO 2 effluxes, mean soil pCO2 was much higher at both Prades sites than at Montseny. Soil pCO2 always increased with depth at Prades while maxima pCO2 at Montseny were often at 20-30 cm depth. A model based on gas diffusion theory was able to explain why soil pCO2 was much higher at Prades than at Montseny, and to reproduce the shape of the vertical profile of pCO2 at the Prades soils. Nevertheless, the model failed to simulate the soil pCO2 maximum found at 20-30 cm depth at the Montseny site. Model simulations using a time-variable CO2 production rate suggested that pCO2 maxima at intermediate depth could be the result of a transient situation instead of an equilibrium one.
Keywords: carbon cycle; Carbon dioxide; Mediterranean ecosystems; soil atmosphere; Soil respiration

CO2 and steam gasification reactions of a charcoal from holm-oak wood. KINETIC AND TEXTURAL CHARACTERIZATION - Valenzuela Calahorro, C; Bernalte García, M J; Serrano Gómez, V; Bernalte García, A (BIOMASS FOR ENERGY AND INDUSTRY: 5th E.C. Conference, 1990)
In this work are shown the kinetic results of carbon dioxide and steam gasification reactions of a charcoal from holm-oak wood and the evolution of some textural parameters (BET surface area, micropore and mesopore volume) of several activated carbons prepared by such reactions
APS
Keywords: activated carbon; Carbon dioxide; charcoal; Holm oak; kinetic; steam gasification